Effects of Ranolazine on Astrocytes and Neurons in Primary Culture - Aldasoro, Martin (Public Library of Science, 2016)
Ranolazine (Rn) is an antianginal agent used for the treatment of chronic angina pectoris when angina is not adequately controlled by other drugs. Rn also acts in the central nervous system and it has been proposed for the treatment of pain and epileptic disorders. Under the hypothesis that ranolazine could act as a neuroprotective drug, we studied its effects on astrocytes and neurons in primary culture. We incubated rat astrocytes and neurons in primary cultures for 24 hours with Rn (10−7, 10−6 and 10−5 M). Cell viability and proliferation were measured using trypan blue exclusion assay, MTT conversion assay and LDH release assay. Apoptosis was determined by Caspase 3 activity assay. The effects of Rn on pro-inflammatory mediators IL-β and TNF-α was determined by ELISA technique, and protein expression levels of Smac/Diablo, PPAR-γ, Mn-SOD and Cu/Zn-SOD by western blot technique. In cultured astrocytes, Rn significantly increased cell viability and proliferation at any concentration tested, and decreased LDH leakage, Smac/Diablo expression and Caspase 3 activity indicating less cell death. Rn also increased anti-inflammatory PPAR-γ protein expression and reduced pro-inflammatory proteins IL-1 β and TNFα levels. Furthermore, antioxidant proteins Cu/Zn-SOD and Mn-SOD significantly increased after Rn addition in cultured astrocytes. Conversely, Rn did not exert any effect on cultured neurons. In conclusion, Rn could act as a neuroprotective drug in the central nervous system by promoting astrocyte viability, preventing necrosis and apoptosis, inhibiting inflammatory phenomena and inducing anti-inflammatory and antioxidant agents.